Pengaruh Mindfulness terhadap Kualitas Hidup pada Wanita dengan Infertilitas - Nisa Amala Muntasya; Finta Isti Kundarti; Indah Rahmaningtyas (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2022)
Infertility is one of the most significant global health problems affecting millions of people of reproductive age, both men and women worldwide. Infertility in women causes poor quality of life. The purpose of this study was to analyze the effect of mindfulness on the quality of life of women with infertility through a systematic review. The method used in the systematic review research is to search through the ProQuest, Wiley Library, Pubmed, Scopus, Science Direct, Sage journal, Cochrane library and Cambridge core databases with the publication year from January 2011 to December 2021. The results obtained are 9 articles that met the inclusion criteria, 5 studies were conducted in Iran, 3 study was conducted in China, 1 study was conducted in London. The use of mindfulness on women with infertility states that mindfulness interventions have an effect on improving the quality of life. Mindfulness in the future can be used as an effective intervention to improve the quality of life in women with infertility. For further studies, it can involve a larger number of samples and can represent the total population so that the results become more valid.